DEVELOPMENT OF TRADITIONAL GAME BOOK AS A MEANS OF IMPROVING THE INTEGRITY CHARACTER OF 10-12 YEARS OLD CHILDREN - Anugrahno, Mey Hawini; Nugrahanta, Gregorius Ari (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2024)
Character education in schools is an important concern due to the moral crisis, especially integrity. The purpose of this research is to develop a traditional game book that can improve the character of integrity in children aged 10-12 years. The research method used is Research and Development with ADDIE type approach. The research participants involved 10 teachers and validators, as well as 8 children in that age range. The results of the guidebook development research were able to prove, 1) the development of guidebook research based on the ADDIE stage, 2) the quality of the product was assessed with a score 0f 3.37 which indicated the quality of â€œVery Goodâ€ and the recommendation â€œNo Need for revisionâ€, 3) the product had a positive impact on the integrity character of children in that age range. The data showed a significant difference between the pretest mean (M = 2.2625, SE = 0.10846) lower than the posttest mean (M = 3.575, SE = 0.03239). significance test t(7) = 0.906 and p = 0,000 (p<0.05). Pearson correlation analysis illustrates the influence of â€œLage Effectâ€, and N-Gain score test showed high effectiveness. Therefore, the developed traditional game book is classified as a very good quality tool and has a positive impact on the integrity character of children aged 10-12 years.